Gene Therapy with a Promoter Targeting Both Rods and Cones Rescues Retinal Degeneration Caused by AIPL1 Mutations - Sun, Xun (2009)
AIPL1 is required for the biosynthesis of photoreceptor phosphodiesterase (PDE)1–3. Gene defects in AIPL1 cause a heterogeneous set of conditions ranging from Leber Congenital Amaurosis (LCA), the severest form of early-onset retinal degeneration, to milder forms such as retinitis pigmentosa (RP) and cone-rod dystrophy1,4,5. In mice, null and hypomorphic alleles cause retinal degeneration similar to human LCA and RP, respectively2,3,6. Thus these mouse models represent two ends of the disease spectrum associated with AIPL1 gene defects in humans. We evaluated whether adeno-associated virus (AAV)-mediated gene replacement therapy in these models could restore PDE biosynthesis in rods and cones and thereby improve photoreceptor survival. We validated the efficacy of human AIPL1 (isoform 1) replacement gene controlled by a promoter derived from the human rhodopsin kinase (RK) gene which is active in both rods and cones7. We found substantial and long-term rescue of the disease phenotype as a result of transgene expression. This is the first gene therapy study in which both rods and cones were targeted successfully with a single photoreceptor-specific promoter. We propose that the vector and construct design used in this study could serve as a prototype for a human clinical trial.